Business Strategy Development of PT DAK (Dok Air Kantung) in Order to be a Market Leader in The Shipyard Industry - Wibowo, Ari; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2013)
The aim of this final project is to find the root of the problems that occur in PT DAK (Dok Air Kantung) that is about the number of shipyard customers from internal PT Timah as a holding of 80% and the number of shipyard customers of the external which is only 20% of total revenue. The root of the problems that wasfound is that the quality of work offered by PT DAK is still less than the expectations of customers, customer complaints are not responded quickly, and the lack of marketing employee that can search the Â external customer. Business strategy of the company must be changed immediately with respect to the shipyard key success factor. Business strategy development method used is the canvas business model, which used nine basic building blocks that must be fixed one by one to obtain the appropriate business strategy with the root problems that occur.Â Keywords: Shipyard, PT DAK, Canvas Business Model, Human Resources.